Words and Numbers: Financialization and Accounting Standard Setting in the United Kingdom - Chahed, Yasmine (Contemporary Accounting Research, 2021)
ABSTRACT How is it possible that British policymakers resisted market‐based measurement for decades while financial economic concepts of decision making and valuation still gained widespread acceptance as a justification for accounting standard setting? This study introduces the concept of “technologies of financialization” to develop the theorizing of the rise of finance in the domain of accounting. Based on a genealogical history of narrative reporting in the United Kingdom, it demonstrates how references to qualitative reporting techniques helped to address recurring crises of measurement from 1969 to 1993, and ultimately contributed to the practical acceptance of market‐based measurement in the UK standard‐setting context. The data are interpreted through a cultural economy framework that directs attention to the power of referring to financial reporting as a combination of words and numbers in sustaining its theoretical redefinition “from below”—that is, by relating it to the experience of practicing accountants rather than accounting theory. As a technology of financialization, narrative reporting made financial economic ideals of market‐based measurement, decision usefulness, and future orientation appear operable in a real‐life reporting context. Whenever measurement reached its practical limits, narratives were relied on to explain the impact of price‐level changes, frame economic decisions, and relate unobservable future cash flows to present‐day strategies and resources. The insight into how narrative reporting practices have been laced into the reasoning of capital markets for over 40 years is timely because it illustrates that narratives can also play a more encompassing role and drive the turn toward wider corporate accountability on social and environmental impacts while hard measurements in this area are still being figured out.